Keefektifan Model Picture and Picture Berbantu Media Gambar Seri Terhadap Ketrampilan Menulis Karangan Narasi Siswa Kelas V SD Negeri Tandang 03 Semarang - Pipit Nabila Fitri; Mei Fita Asri Untari; Sukamto Sukamto (STKIP Andi Matappa Pangkep, 2021)
The background in this study is that students are less able to develop a writing and are still not careful in writing, ideas and ideas or descriptions that will later be contained in the writing are not fully able to be done by grade V students of Tandang Elementary School 03 Semarang when given the task of making narratives and learning which is still centered on the teacher so that students become passive in participating in learning. This type of research is a quantitative study using a pretest-posttest one-group design. The results of the data analysis of the pre-test and post-test learning outcomes with the t-test were obtained with an average pretest score of 50.14 and an average posttest score of 80.35. With N = 28, obtained tcount = 13.6706 with a significant level of 5% of 2.0484. Because tcount = 13.6706> ttable = 2.0484, then this shows that the t test has a significant effect. This shows that there is an effect of learning the Picture and Picture Model. This research can be concluded that the Picture And Picture Model is effective on the speaking ability of fifth grade students at SD Negeri Tandang 03 Semarang.